Special Issue Robótica 2014 - Lau, Nuno (2019)
This special issue presents extended and revised versions of a selection of papers presented on the IEEE International Conference on Autonomous Robot Systems and Competitions (ICARSC-2014), that took place 14-15 May 2014 in the city of Espinho, Portugal.